Analisis Sistem Informasi Inventory Menggunakan Metode Waterfall Berbasis Web - Daviqia Fadel; Deryl Iman Condro Baskoro (PT Jurnal Cendekia Indonesia, 2025)
This research aims to develop a web-based inventory information system using the Waterfall method. This system is designed to overcome problems in stock management, such as inaccurate recording, late information, and lack of operational efficiency. The Waterfall method is used because of its systematic and structured development flow, starting from needs analysis to the maintenance stage. This system includes main features such as registration, login, management of goods data, categories, stocks, and creation of printable reports. Testing shows that all features run according to user needs and are free from bugs. With an easy-to-use interface and real-time access capabilities, this system is expected to improve the efficiency and accuracy of inventory management in the organization.